2019
DOI: 10.1158/1538-7445.am2019-3077
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3077: Preclinical studies of SR-8314, a highly selective ENPP1 inhibitor and an activator of STING pathway

Abstract: Purpose: STING (stimulator of interferon genes) plays an important role in innate immunity by activating type I interferons in response to cytosolic nucleic acid ligands such as cyclic dinucleotides (CDNs). In recent years, STING has become an attractive therapeutic target for cancer immune therapy and hydrolysis resistant CDNs have been developed as a new class of cancer therapeutics. These CDNs have been shown to possess potent preclinical efficacy but early results from phase I trials have been disappointin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Among these, meta-pyridine substituted compound 7c was the most potent compound, with a K i of 58 nM (0.058 µM) [85]. More recently, Weston et al reported a new ENPP1 inhibitor, SR-8314, which promotes STING activation [86]. The K i value of SR-8314 against ENPP1 activity was reported as 0.079 µM.…”
Section: Inhibitors Of Enpp1mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, meta-pyridine substituted compound 7c was the most potent compound, with a K i of 58 nM (0.058 µM) [85]. More recently, Weston et al reported a new ENPP1 inhibitor, SR-8314, which promotes STING activation [86]. The K i value of SR-8314 against ENPP1 activity was reported as 0.079 µM.…”
Section: Inhibitors Of Enpp1mentioning
confidence: 99%
“…The K i value of SR-8314 against ENPP1 activity was reported as 0.079 µM. It was also shown that SR-8314 has anti-tumor activity with more CD3 + , CD4 + , and CD8 + T cells found in SR-8314 treatments compared to controls [86]. Baird et al developed another selective ENPP1 inhibitor, MV-626, which prevents the hydrolysis of cGAMP, and increases STING activation [87].…”
Section: Inhibitors Of Enpp1mentioning
confidence: 99%
“…SR-8314 and SR-8291 are both highly selective ENPP1 inhibitors that have shown promising in vivo efficacy in syngeneic murine tumor models. Intraperitoneal injection of SR-8314 and SR-8291 led to increased frequencies of CD4 + and CD8 + T cells and a decrease in tumor-associated macrophages in tumor-bearing mice [ 97 ]. SR8541A is another small molecule ENPP1 inhibitor which in recent in vitro studies has been shown to stimulate the migration and infiltration of peripheral blood myeloid cells into the tumor microenvironment [ 96 ].…”
Section: Sting Agonists In Pre-clinical Evaluationsmentioning
confidence: 99%
“…Antitumor activity of SR-8314 was confirmed in a syngeneic murine tumor model, and increased levels of CD3 + , CD4 + , and CD8 + T cells were observed in SR-8314-treated tumors. 90 SR-8541A is also a potent ENPP1 inhibitor that triggers strong immune responses, which are indicated by the amplified expression of IFN-β, ISG15, and CXCL10. An immune infiltration study showed that treatment with SR-8541A stimulated the migration and infiltration of peripheral blood myeloid cells into tumors.…”
Section: Enpp1 Inhibitors In Clinical and Preclinical Studiesmentioning
confidence: 99%